SEJARAH GERAKAN KEMANUSIAAN (STUDI KASUS PALANG MERAH INDONESIA DI BANDUNG) 1945 – 2022 - Muhamad Fajar Ramdhan (UIN Sunan Gunung Djati Bandung, 2025)
The existence of wars that occurred from around the world in ancient times caused many casualties. One such battle was between French and Italian troops fought against Austrian troops. This war gave birth to many casualties, one who was heading to a place to start a business instead saw many victims of war who were helpless. He was moved to help by inviting the surrounding community to help the wounded soldiers. In its development, in every country a volunteer organization was established. The organization is called the international association of red cross and red crescent. In Indonesia, it actually started before the Second World War. The Dutch colonial government established the organization under the name Nederlands Rode Kruis Afdeling Indie (Nerkai). However, during the Japanese occupation, the organization was disbanded. At the time after the proclamation of independence, President Soekarno issued an order to form a national red cross body. In the end the Indonesian Red Cross was formed after 1 month of independence to be precise on September 17, 1945. The researcher aims to let the general public know that the humanitarian movement was born in ancient times, with this paper the author hopes to awaken people's hearts to be able to help regardless of race, ethnicity and religion.